Composition and Acidification of the Culture Medium Influences Chronological Aging Similarly in Vineyard and Laboratory Yeast - Murakami, Christopher J. (Public Library of Science, 2011)
Chronological aging has been studied extensively in laboratory yeast by culturing cells into stationary phase in synthetic complete medium with 2% glucose as the carbon source. During this process, acidification of the culture medium occurs due to secretion of organic acids, including acetic acid, which limits survival of yeast cells. Dietary restriction or buffering the medium to pH 6 prevents acidification and increases chronological life span. Here we set out to determine whether these effects are specific to laboratory-derived yeast by testing the chronological aging properties of the vineyard yeast strain RM11. Similar to the laboratory strain BY4743 and its haploid derivatives, RM11 and its haploid derivatives displayed increased chronological life span from dietary restriction, buffering the pH of the culture medium, or aging in rich medium. RM11 and BY4743 also displayed generally similar aging and growth characteristics when cultured in a variety of different carbon sources. These data support the idea that mechanisms of chronological aging are similar in both the laboratory and vineyard strains.